PENGARUH PELATIHAN DAN PENGEMBANGAN DAN JABATAN FUNGSIONAL TERHADAP MOTIVASI BERPRESTASI DOSEN PERGURUAN TINGGI SWASTA - Effiyaldi . (Jurnal Dinamika Manajemen, 2014)
The Low of lectures achievement motivation at the Private Higher Education (PTS) is the focus of this research. After implemented survey, it is found that 39.7% of training and development activities con-tributed to achievment motivation, whereas contibution of lecturer function is 34 %. According to statistical examination, lecturer functional has more significant influnced on achievment motivation. Hence, lecturer funtional development is one of the strategies to improve achievment motivation. Keywords. Training Â and development, functional positions, and achievment motivation.